What, if anything, are species?. - Mishler, Brent Drennen, 1953- (Boca Raton : CRC Press, 2021)
This book is an extended argument for abandoning the species rank. Instead, the author proposes that the rank of "species" be replaced by a pluralistic and multi-level view. In such a view, all clades including the smallest identifiable one would be named and studied within a phylogenetic context. What are currently called "species" represent different sorts of things depending on the sort of organisms and processes being considered. This is already the case, but is not formally recognized by those scientists using the species rank in their work. Adopting a rankless taxonomy at all levels would enhance academic studies of evolution and ecology and yield practical benefits in areas of public concern such as conservation. KEY FEATURES Proposes the replacement of restrictive species concepts with a pluralistic view Suggests abandoning the formal taxonomic rank of "species" Considers zoological, botanical, and microbiological aspects of the species level Deals with practical issues such as conservation, inventories, and field guides
Brent Mishler is Director of the University and Jepson Herbaria at UC Berkeley, as well as a professor in the Department of Integrative Biology, where he teaches systematics and plant diversity. A native southern Californian, he attended Bonita High School in La Verne, California and worked for Los Angeles County as a ranger-naturalist at San Dimas Canyon County Park, where he became interested in natural history and especially botany. He attended California State Polytechnic University, Pomona, where he received his B.S. degree in Biology in 1975 and his M.S. in biology in 1978. He then received his Ph.D. from Harvard University in 1984, and was on the faculty at Duke University in Durham, NC for nine years before moving to UC Berkeley in 1993.
Keywords: Species; NATURE / Animals; SCIENCE / Life Sciences / Botany; SCIENCE / Life Sciences / Evolution; Species; Electronic books